Destino dos resíduos gerados pela construção civil na cidade do Assú – RN - Lopes, Messias Esthfâni Fonsêca Vicente (Universidade Federal Rural do Semi-Árido, 2018)
Due to the accelerated process of urbanization and the rapid growth of cities, the construction sector had a great role for the economic and social development of the country. This led to a number of issues regarding Civil Construction Waste (RCC), due to the exaggerated consumption of raw material as well as to the impacts caused by the bad deposition of the waste. In surveys carried out in some Brazilian municipalities, the amount of waste composes a large portion of urban solid waste. The objective of this work was to obtain information on the destination of construction waste in the municipality of Assú / RN, in addition to identifying the possible social and environmental impacts caused to the city. After a thorough bibliographic study about the RCC, a questionnaire was applied between February and March of 2018 in the construction companies with headquarters in the city. The aim of this work was to know the treatment and the use of RCC in the construction sites and their possible reuse, knowing the benefits of good reuse practice and the damages of the poor deposition of this waste in places that are inappropriate for society and environment. The lack of a Municipal Solid Waste Management Plan favors the municipality to discard RCCs in inappropriate areas, thus generating socio-environmental problems for the local population
Monografia
Keywords: Resíduos de construção civil; Poluição visual; Impactos ambientais; Entulhos de obra; Civil construction waste; Visual pollution; Environmental impacts; Debris; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA